PENYULUHAN DAN EDUKASI PENCEGAHAN STUNTING DI DUSUN CICADAS DAN JAMPANGMANGGUNG DESA MALABAR KECAMATAN WANAREJA - Rahmawati, Rahmawati; Fitriani, Windi; Malinda, Dini; Anita, Nita; Afifah, Fitri Nur; Febriyanti, Winda; Puspitasari, Mela (Universitas Bakti Tunas Husada, 2024)
Stunting, caused by nutritional deficiencies and inhibited infant growth, is a serious issue impacting the health and development of children. The objective of this initiative is to provide counseling and education to the community in Cicadas and Jampangmanggung Hamlets, Malabar Village, Wanareja District, on stunting prevention. The method employed in this activity involves counseling sessions for 34 respondents with varying educational backgrounds (elementary, junior high, high school, undergraduate). Additionally, informative leaflets were distributed to the community, and they were asked to fill out a questionnaire comprising 10 questions related to stunting. The community showed great enthusiasm for this initiative, leading to a paired T-Test analysis yielding a p-value of (0.000), indicating a significant difference in average values before and after the counseling sessions. This demonstrates that the counseling and educational efforts regarding stunting prevention have enhanced the community's understanding of stunting prevention and have the potential to reduce stunting rates